I have no idea how the author got from $$E[(pe^s+(1-p)e^t)^x]\rightarrow e^{\lambda(pe^s+(1-p)e^t-1)}$$

The author writes $a=e^t$, and then sets $a=pe^s+(1-p)e^t$ and plugs it in where $e^t$ normally goes in a Poisson moment function.

Why does this make sense? I don't get how $e^t=pe^s+(1-p)e^t$

textbook question+answer

  • $\begingroup$ I cannot find in the proof what you describe. Which of the equalities mentioned in the proof is unclear to you? $\endgroup$ – drhab May 22 '18 at 11:36
  • $\begingroup$ The part where they plug into the poisson moment function $\endgroup$ – Frank May 22 '18 at 17:13

If $X$ has Poisson distribution with parameter $\lambda$ then: $$\mathbb Ee^{tX}=e^{\lambda(e^t-1)}\text{ for every }t\in\mathbb R\tag1$$

This can also be written as $\mathbb E(e^t)^X=e^{\lambda(e^t-1)}$ and substitution $a=e^t$ then tells us that $(1)$ is the same statement as: $$\mathbb Ea^X=e^{\lambda(a-1)}\text{ for every }a>0\tag2$$

This means that we can substitute for $a$ every expression that results in a positive real number and we choose for the expression $pe^s+(1-p)e^t$.

This gives us the result:$$\mathbb E(pe^s+(1-p)e^t)^X=e^{\lambda(pe^s+(1-p)e^t-1)}\tag3$$

It has been shown earlier in the proof that the LHS of this equality equals $\mathbb E(e^{sX_c+t(X-X_c)})$.

Further the RHS of the expression equals $e^{\lambda p(e^s-1)}e^{\lambda (1-p)(e^s-1)}$.

So our final result is:$$\mathbb E(e^{sX_c+t(X-X_c)})=e^{\lambda p(e^s-1)}e^{\lambda (1-p)(e^s-1)}\tag4$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.